Product Quality, Digital Marketing, and Content Marketing Effects on Visitor Decisions at Saung Jembar - Syalwa Nazhifah Aulya Wanda; Ezra Karamang; Ridlwan Muttaqin (International Journal of Multidisciplinary Sciences and Arts, 2026)
The development of digital technology has changed the way consumers make purchasing decisions, especially in the culinary and tourism sectors. This study aims to analyze the influence of product quality, digital marketing, and content marketing on visitor decision-making at Saung Jembar, Tasikmalaya Regency. This study uses a quantitative approach with a descriptive-verificative method, where data is collected through questionnaires distributed to 85 visitors to Saung Jembar. Data analysis is carried out using multiple linear regression tests to examine the influence of the three variables on visitor decisions. The results show that product quality has a significant influence on visitor decisions, with food taste and product consistency as the dominant factors in creating a positive experience. Digital marketing also has a positive effect, although overly frequent promotions can reduce its effectiveness. Content marketing, especially through storytelling and authentic visual content, has been proven to have a significant influence on visitor decisions. Simultaneously, these three variables explain 95.6% of the variation in Saung Jembar visitors' decision-making. In conclusion, the success of Saung Jembar's marketing strategy is highly dependent on the synergy between product quality and effective and authentic digital marketing. This study recommends that Saung Jembar pay more attention to the alignment between expectations built through digital promotions and the reality on the ground, as well as improving the quality of content to make it more attractive and relevant in order to attract more visitors.